Photoredox-Catalyzed Decomposition of Nitric Oxide over Au-Enhanced Surface Plasmon Resonance ZnSn(OH)6 Microcubes - Minh-Thuan Pham; Truc Mai Thi Nguyen; Sheng-Jie You; Ya-Fen Wang (Aerosol and Air Quality Research)
Abstract Air pollution is one of the most concerning issues today because of its adverse effects on living organisms and the environment. Therein, nitric oxide (NO) is the leading cause of the greenhouse effect, acid rain, and respiratory diseases. Therefore, discovering a low-cost, environmentally friendly, highly efficient photocatalysis technique to remove NO is necessary and urgent. In this work, the ZnSn(OH)6 microcubes (cZHS) catalyst was decorated with golden nanoparticles (Au:cZHS) to enhance the photoredox-catalyzed degradation of NO under solar light by surface plasmon resonance (SPR). This work demonstrated the contribution of SPR to the photoredox performance of the ZHS. Herein, the photoredox efficiency of the cZHS increased dramatically under the effecting of SPR from the golden nanoparticles, the photoredox efficiency of the Au:cZHS reached 75%, about four times higher than that of cZHS. In addition, the generation of other nitrogen species, nitrogen dioxide (NO2) conversion, and the reusability of the materials are calculated and discussed carefully by theory and experiment. On the other hand, the contribution and lifespan of radicals are also investigated clearly with trapping experiments and time-dependent electron spin resonance (ESR). This study provided the reader with a clear understanding of the SPR effect on the photocatalytic performance of cZHS, which may be necessary for future related studies.